ANALISIS PEMBANGUNAN EKOWISATA DI KAWASAN TAMAN HUTAN RAYA BERBASIS SISTEM INFORMASI GEOGRAFIS (Studi Kasus Pada Blok Pembangunan Wisata Ngata Baru Kabupaten Sigi - Riyanto, Riyanto; Hamzari, Hamzari; Golar, Golar (Jurnal Warta Rimba, 2014)
Central Sulawesi is one of the areas that have the potential forest to be utilized as an area of ecoturism. The business through the utilization of forest conservation is the conservation of nature as an object of tourist areas in economic development without ignoring the environmental ecosystem function.This study aims to Analysisecotourims block Development of Tahura based on the System infomation Geografis.Data was analysis consisted of quantitative and qualitative approache`s,as well as interviews and discussions about the desires and expectations of the community in the development of natural attractions including the Ecotourism. The research conclusions that Ngatabaru region Ecotourism development can be summarized as follows: Block Ecotourism in Ngatabaru are in accordance with the criteria and indicators of eco-tourism development, including: land Criticality, Accessibility, topography/slope, community support, security, availability of water resources, and conflict of interest, the pattern of utilization of existing space is currently set up with a structure that is divided into several blocks, ranging from natural scenery, family travel, educational activities, outbon, and meeting place Keywords :Analysis, Ecotourism, Tahura, GIS, Ngatabaru